Perkembangan Pandemic Dan Capaian Kontrasepsi Di Provinsi Jawa Timur - Kurniawan, Afif; Herowati, Diyah; Yuliani, Cahya; Putri, Linta Meyla; Mamesah, Marline Merke; Amalia, Nuke; Mardiana, Mardiana; Goenarso, Roberto A; Tjokro, Silvia Haniwijaya; Wijaya, Hermanto (Indonesian Academia Health Sciences Journal, 2023)
The impact of the Covid-19 pandemic is being felt all over the world, especially in Indonesia. Covid-19 has had an impact on the health, economic and social sectors. The large number of deaths due to disease causes changes in the composition of the population. To prevent the spread from becoming more widespread, the government implemented large-scale social restrictions. Travel restrictions and long stays at home have the government fearing a post-pandemic boom in births. Therefore the government focuses on birth control. This study aims to determine the development of a pandemic and its impact on the number of new users of family planning methods in East Java Province.The research used secondary data that came from the website of the East Java Provincial Health Office and the Population and Family Planning Agency from March 2020 to November 2021. The results of the regression test showed that there was no effect between the number of positive confirmed cases of Covid-19 and the number of new users of contraceptive methods. This shows that the policies developed have been successful and it is hoped that there will be a strategy for family planning services for other emergencies. Socialization and establishing cooperation between health workers in the field also need to be improved, especially for health workers in the private sector.